P-025 Interventional Treatment of High Flow Craniofacial Vascular Malformations. (26th July 2014) - Dabus, G; Linfante, I; Lin, E; Benenati, J; Martínez-Galdámez, M
Abstract : Objective: High flow craniofacial vascular malformations are uncommon lesions that pose a very difficult therapeutic challenge. They are locally aggressive lesions that can present in several different ways from completely asymptomatic lesions to significant bleeding, pain, neuropathy, tissue destruction or congestive heart failure. Several therapeutic strategies have been proposed including surgery, embolization or a combination of both. We report our experience in the treatment of high flow craniofacial vascular malformations. Methods: The neurointerventional databases of 2 institutions were retrospectively reviewed from October of 2010 to March of 2014. All patients with high flow craniofacial vascular malformations were included in the analysis. Clinical presentation, location, type, agent and techniques used, procedural complications, clinical and imaging follow ups were included in the analysis. Results: Among the patients in our neurointerventional databases, 16 patients (11 females and 5 male) met the inclusion criteria in our study. Patients' ages ranged from 4 to 66 years old (mean 45.2 years). All patients were symptomatic (pain, bleeding and mass/disfigurement were the most prevalent symptoms). One patient had 2 separated arteriovenous malformations (one nasal and the other forehead/scalp). One patient with a nasal arteriovenous malformation had CM-AVM syndrome. Overall, there were 12 arteriovenous malformations and 5 arteriovenous fistuli treated in 26 embolizations procedures (ranging from 1 procedure to 4 procedures; mean 1.6 procedures). Onyx was the predominant agent used in 20 procedures. Two procedures were done using predominantly ETOH; 2 procedures were done using predominantly nBCA; and 2 procedures used only coils/particles. One procedure was performed using only transvenous route; direct puncture was the only access in 9 cases; transarterial technique was the only route in 12 procedures; and 4 procedures used combine transarterial and direct puncture techniques. In 26 procedures there was one procedural complication (skin ulceration). At the end of last treatment session 10 out of 16 patients had angiographic cure or minimal residual vascular malformation (5 AVFs and 5 AVMs). Symptomatic control was achieved in all cases with all patients stating that the symptoms had resolved or significant improvement (mean follow up 8 months). Five patients underwent scheduled surgery to remove the arteriovenous malformations. Conclusions: In summary, high flow craniofacial vascular malformations are challenging diseases that can be successfully managed with interventional techniques providing symptomatic control. Disclosures: G. Dabus: 2; C; Covidien, Microvention, Reverse Medical. 4; C; Surpass Medical. I. Linfante: 2; C; Covidien, Stryker, Codman. 4; C; Surpass Medical. E. Lin: None. J. Benenati: 2; C; Gore, Cook, Penumbra, Covidien, Reverse Medical, Cordis, Surefire, Abbott, Angio Dynamics, MC-10. M. Martínez-Galdámez: 2; C; Covidien.